1996
DOI: 10.1074/jbc.271.34.20246
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation and Activation of Myosin by Rho-associated Kinase (Rho-kinase)

Abstract: The small GTPase Rho is implicated in physiological functions associated with actin-myosin filaments such as cytokinesis, cell motility, and smooth muscle contraction. We have recently identified and molecularly cloned Rho-associated serine/threonine kinase (Rho-kinase), which is activated by GTP⅐Rho (Matsui, T., Amano, M., Yamamoto, T., Chihara, K., Nakafuku, M., Ito, M., Nakano, T., Okawa, K., Iwamatsu, A., and Kaibuchi, K. (1996) EMBO J. 15, 2208 -2216). Here we found that Rhokinase stoichiometrically phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

35
1,476
3
9

Year Published

1998
1998
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 1,837 publications
(1,523 citation statements)
references
References 41 publications
35
1,476
3
9
Order By: Relevance
“…Signaling through its effectors Rho kinase (ROCK) and mDia, Rho stimulates actin stress fiber formation by stimulating the monomeric actin binding protein profilin, and stabilizes stress fibers by inhibiting the activity of the actin depolymerizing protein, cofilin [35][36][37][38][39][40]. Bundling of actin filaments with myosin to form stress fibers, itself stimulated by ROCK and myosin light chain kinase, stimulates cell contraction and stabilization of focal adhesions [41][42][43][44], points of integrin-extracellular matrix contact between the ventral surface of the cell and the underlying substrate. Rho-mediated contractility is important for retraction of the cell rear and translocation of the cell body [26].…”
Section: Rho Family Gtpases Regulate Actin Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Signaling through its effectors Rho kinase (ROCK) and mDia, Rho stimulates actin stress fiber formation by stimulating the monomeric actin binding protein profilin, and stabilizes stress fibers by inhibiting the activity of the actin depolymerizing protein, cofilin [35][36][37][38][39][40]. Bundling of actin filaments with myosin to form stress fibers, itself stimulated by ROCK and myosin light chain kinase, stimulates cell contraction and stabilization of focal adhesions [41][42][43][44], points of integrin-extracellular matrix contact between the ventral surface of the cell and the underlying substrate. Rho-mediated contractility is important for retraction of the cell rear and translocation of the cell body [26].…”
Section: Rho Family Gtpases Regulate Actin Dynamicsmentioning
confidence: 99%
“…Activation of Rho stimulates contractility and focal adhesion formation by promoting bundling of actin filaments and associated myosin motors into stress fibers [44]. Rho-ROCK signaling influences contraction through effects on both the myosin and actin: ROCK elevates myosin light chain phosphorylation by inhibiting myosin phosphatase and/or by directly phosphorylating myosin light chain (MLC) [41][42][43]. ROCK also phosphorylates and activates LIM kinase [64], which in turn phosphorylates and inactivates the actin severing protein, cofilin [36,65].…”
Section: Focal Adhesion Dynamicsmentioning
confidence: 99%
“…Both inhibitors exhibited similar dose-dependent inhibition profiles with nearly identical IC 50 values (Figure 1), even though the K i values for the pure form of MLCK are about 10-fold different between the two compounds. 12 Although these drugs have inhibitory effects on other protein kinases besides MLCK, 4,[13][14][15][16] it is likely that the reduction of MLL cell invasion is due to the impairment of MLCK, as the affinity of both drugs is at least eightfold higher towards MLCK than other enzymes (viz. K i value of ML-9 for protein kinase A ¼ 32 mM, whereas that for MLCK ¼ 3.8 mM).…”
Section: Metastatic Cancer Cell Invasionmentioning
confidence: 99%
“…So far, myosin binding subunit of myosin phosphatase , myosin light chain (MLC; Amano et al, 1996), ezrin/radixin/moesin (ERM) proteins (Matsui et al, 1998;Fukata et al, 1998), adducin , GFAP (Kosako et al, 1997) and vimentin (Goto et al, 1998) have been identi®ed as the putative physiological substrates for Rho-kinase. Especially, ERM proteins (Sato et al, 1991) and Ser 19 -phosphorylated MLC (Matsumura et al, 1998; Rho-kinase phosphorylates MLC at Ser 19 in vitro; Amano et al, 1996) have been shown to be highly concentrated at the cleavage furrow.…”
mentioning
confidence: 99%